Mathematics: contextualization, sociocultural and environmental limits of its application in the students' everyday lives - Rosineide Xavier Figueiredo; Milton Ferreira da Silva Júnior (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
The environmental issues have been the subject of study and concern in the contemporary society. In its turn, education changes the ways of thinking and acting of the individuals through a contextualized and interdisciplinary teaching, awakening them to a critical sense. Taking this into account, this research studied specifically mathematics, which is not only the logical reasoning science but also an instrument which can be used by man to interfere in the building of a society based on his interpretation of nature in order to achieve a sustainable life. It also sought to inquire into the social and cultural limits of the introduction of the environmental practice in Mathematics teaching in order to reach what Capra (1969) calls "Ecological Literacy". The survey was carried out with first and fourth-grade students of the Integrated Mode Courses in the Federal Institute of Education, Science and Technology of Bahia (IFBA), campus Vitoria da Conquista, during the month of December 2011. As it was a quantitative research, a questionnaire was applied and the collected data made it possible to reach results that generated proposals for changes in teaching and learning not only mathematics but also other disciplines, aiming to contribute to the development of attitudes and values concerning the human behavior.